Prognostic Nomogram for Acute Myeloid Leukemia Patients With Biallelic CEBPA Mutations - Xu, Xiaoyu; Cai, Wenzhi; Cai, Ping; Zhang, Ling; Yao, Hong; Zhang, Tongtong; Shen, Hongjie; Chen, Suning (Frontiers in Oncology, 2021)
Adult acute myeloid leukemia (AML) patients with biallelic mutations of CEBPA (biCEBPA) displays a favorable clinical outcome, and is defined as a unique entity in the 2016 World Health Organization classification. However, due to the intrinsic characteristics of the mutation, existence of co-occurring mutations and diversified gene expression signature, the prognosis of these patients needs to be analyzed in a more systematic way. In this study we evaluated the genetic characteristics and clinical outcome in a cohort of 137 biCEBPA AML cases, and proposed a prognostic nomogram to predict the overall survival (OS) of based on the clinical variables selected by multivariate Cox regression model in training cohort, including age, white blood cell count, co-existence of DNMT3A and CSF3R mutation and whether patients could achieve complete remission after induction therapy. The area under the receiver operating characteristic (ROC) curves for 3 and 5-year OS were 0.833 and 0.863, respectively. RNA sequencing of 4 relapsed patients showed that over-expression of VMP1 was an indicator of poor prognosis of biCEBPA AML patients. In conclusion, this prognostic nomogram might provide a more accurate prediction of the clinical outcomes of biCEBPA AML patients.